Novel trimethoprim resistance gene, dfrA35, in IncC plasmids from Australia. (15th April 2019) - Ambrose, Stephanie J; Hall, Ruth M
Abstract: Background: In Gram-negative bacteria, over 30 different genes are known to encode a trimethoprim-insensitive dihydrofolate reductase that confers resistance to trimethoprim. Objectives: To determine whether a gene encoding a putative dihydrofolate reductase found in type 2 IncC plasmids isolated between 2002 and 2013 in healthcare facilities in Melbourne, Australia, confers trimethoprim resistance. Methods: Conjugation was used to transfer plasmids into a laboratory Escherichia coli . A PCR-amplified fragment was cloned into pUC19 using Gibson Assembly and transformed into E. coli . The level of resistance to trimethoprim was determined using broth microdilution. MEGA (7.0.26) and Geneious Prime (7.0.9) were used to examine the relationship to known Dfr proteins. Results: The conjugative IncC plasmid pEc158 from a 2002 Melbourne clinical E. coli isolate was shown to transfer trimethoprim resistance. The putative DfrA protein encoded by a dfrA gene in pEc158 shares <40% amino acid identity with any previously identified DfrA protein. This gene was cloned and found to confer trimethoprim resistance. The gene and protein were named dfrA35 /DfrA35. In pEc158 the dfrA35 gene is located near the ori end of a partial copy of the CR1 element, within a complex resistance island. It is found in the same location in further closely-related type 2 IncC plasmids from Klebsiella pneumoniae (Melbourne, 2013), which were not transfer proficient. Conclusions: Resistance determinants continue to be found and will be missed using website-associated databases to infer phenotypes from genome sequences rather than direct phenotypic testing.